Application of Digital Teaching Materials Based on Flipped Learning Model in Civics Education in Elementary School - Waldi, Atri; Supendra, Dedi; Rivelia, Katherine Putri; Anggraeni, Aisyah; Febriani, Rika (JOIV : International Journal on Informatics Visualization, 2025)
This research aims to improve students' understanding of Pancasila Student Profile Values through the implementation of Flipped Learning by combining it with digital teaching materials according to the characteristics of students in elementary schools. In addition, this research also aims to create practical digital teaching materials for elementary school students in Padang City on Civic Education learning. This research is a development research using the 4D development model (Define, Design, Develop and Disseminate). This study involved a sample of elementary school students in Padang City who measured the practicality of the developed teaching materials assessed through a structured evaluation process. The results showed a high practicality score of 96%, which categorized the digital teaching materials as very practical for use in the classroom. In addition, researchers also measured the impact of the implementation of these teaching materials on student learning outcomes by obtaining significant results; 87% of students achieved scores above the threshold of completeness, with an average score of 88. The findings suggest that the integration of Flipped Learning with digital teaching materials not only facilitates a deeper understanding of Pancasila values but also positively affects students' overall performance. The implications of this study highlight the potential for further research to explore the long-term effects of digital teaching materials and Flipped Learning on different subjects and levels of education. Future research could also investigate the scalability of these materials in different educational contexts and their effectiveness in fostering critical thinking and civic engagement among students.